Application of Audio-Visual Media in the Hannafin and Peck Instructional Model for Islamic Religious Education - Yusuf Pardamean; Mulyawan Safwandy Nugraha; Ghozyudin Fawaz (KEDJATI Journal of Islamic Civilization, 2026)
Instructional media play a vital role in the teaching and learning process by facilitating the delivery of learning materials and reducing ambiguity in students' understanding. Among various instructional media, audio-visual media have been widely recognized for enhancing student engagement and learning effectiveness. This study aims to examine the implementation of audio-visual media within the Hannafin and Peck instructional model in Islamic Religious Education learning. The study employs a qualitative library research design, complemented by interview and observation data to enrich the analysis. Data were collected from scholarly sources, including journal articles, theses, books, and other relevant publications addressing instructional media, learning theories, and the Hannafin and Peck instructional model. The findings indicate that integrating audio-visual media into the Hannafin and Peck instructional model enhances the effectiveness of Islamic Religious Education by promoting active learning, improving students' comprehension of abstract concepts, and supporting systematic instructional design. These findings suggest that the combination of audio-visual media and the Hannafin and Peck model provides a practical instructional framework for improving teaching and learning outcomes in Islamic Religious Education.